(untitled) (Journal of Peace, Security and Democracy, 2026)
Across many electoral democracies in sub-Saharan Africa, persistent insecurity challenges the assumption that democratic governance inherently promotes peace. Nigeria exemplifies this paradox, where repeated electoral cycles coexist with escalating violence, including insurgency, banditry, and communal conflict. While existing studies emphasise structural drivers such as poverty and weak institutions, less attention has been paid to how citizens’ perceptions of democratic failure shape pathways to violence. This study examines the micro-foundations of armed mobilisation by analysing how democratic disillusionment influences individual and collective engagement with non-state violence in Nigeria. It asks: (1) How do citizens interpret and respond to perceived failures of democratic governance? and (2) How do these perceptions affect their willingness to support or participate in violent alternatives? The study adopts a qualitative research design based on secondary data, drawing on policy reports and existing scholarly literature. Using a thematic and interpretive analytical approach, it traces the relationship between perceived democratic exclusion, declining institutional trust, and patterns of armed mobilisation. The study demonstrates that insecurity is not only a product of structural deprivation but also of legitimacy crises that reshape citizens’ calculations about authority and participation. By foregrounding perception and agency, the study advances a more nuanced understanding of the democracy–security nexus. The study contributes to debates on the democracy–security nexus by demonstrating how legitimacy crises at the citizen level can translate into support for, or participation in, non-state violence. Keywords: Armed mobilisation; Democratic disillusionment; Legitimacy; Nigeria; Peace and security